Pengembangan Sistem Manajemen Kerja Daring Karyawan pada Hubungan Kerja Antara Atasan dan Bawahan (Studi Kasus: CV Dias Putra) - Yufita Berliana Putridewati; Achmad Arwan; Agi Putra Kharisma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The applied solution as prevention of distribution pandemic Coronavirus Disease (Covid-19) in the office and company clusters is working online. Today's CV Dias Putra company implements a policy of working online on some of its employees. These employees who work in the office including administrative and finish goods employees, general employees, accounting employees, finance employees, marketing employees. During the covid-19 pandemic, the company has not implemented employee online work management in a structured and systematic way so that this makes it difficult to manage data such as employee's data, attendance's data, assigning assignments, uploading work reports, and evaluating employee performance. To make easier and help the work process of employees who work online, a solution is needed by develop a web based management working online on work relationships between Superiors and Subordinates that can can organize/manage employees to be structured and systematic which includes attendance data management, assignment assignments, uploading work reports, and evaluating employee performance. The system development uses waterfall models, then the implementation system uses MongoDB in the database and PHP language with the codeigniter framework as a programming language. Functional requirement has been tested by unit testing, integration testing, validation testing from 45 test case with result 100% passed, And non-functional testing has been tested by compatibility testing.